2003
DOI: 10.1002/path.1408
|View full text |Cite
|
Sign up to set email alerts
|

Imbalanced secondary mucosal antioxidant response in inflammatory bowel disease

Abstract: Intestinal mucosal damage in the inflammatory bowel diseases (IBD) Crohn's disease (CD) and ulcerative colitis (UC) involves reactive oxygen metabolites (ROMs). ROMs are neutralized by endogenous antioxidant enzymes in a carefully balanced two-step pathway. Superoxide dismutases (SODs) convert superoxide anion to hydrogen peroxide (H(2)O(2)), which is subsequently neutralized to water by catalase (CAT) or glutathione peroxidase (GPO). Remarkably changed expression levels of the three isoforms of SOD in paired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
137
1
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(153 citation statements)
references
References 36 publications
13
137
1
2
Order By: Relevance
“…ClCa4 is considered to be an important molecule for the induction of diarrhea in cystic fibrosis (19). Gpx2 is a marker for the colonic inflammation that occurs in experimental colitis and inflammatory bowel diseases (20)(21)(22). It has been suggested that all of these molecules are involved in the pathogenesis of inflammatory changes in the intestine.…”
Section: Discussionmentioning
confidence: 99%
“…ClCa4 is considered to be an important molecule for the induction of diarrhea in cystic fibrosis (19). Gpx2 is a marker for the colonic inflammation that occurs in experimental colitis and inflammatory bowel diseases (20)(21)(22). It has been suggested that all of these molecules are involved in the pathogenesis of inflammatory changes in the intestine.…”
Section: Discussionmentioning
confidence: 99%
“…There are studies in the literature that reports inflammatory cytokines such as TNF-α and IL-1 play role in the etiology of IBD [11][12][13][14] . TNF-α is the most important cytokine in inflammatory process.…”
Section: Discussionmentioning
confidence: 99%
“…MPO, MDA, NO, Caspase-3, IL-6 and TNF-α were analyzed. The tissues were rinsed with serum physiologic for the biochemical analysis and then weighted and homogenized using the method by previously described 12 . Tissue samples (distal colon) were obtained from the rats for biochemical examination.…”
Section: Biochemical Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive liberation of RONS by polymorphonuclear cells is considered the main mechanism for colonic lesion in ulcerative colitis (UC), where accentuated lipid peroxidation occurs (48) . It has also been suggested that imbalanced and inefficient endogenous antioxidant response, especially attributed to SOD dual role acting as superoxide anion scavenger and an H 2 O 2 producer, may contribute to both the pathogenesis and the perpetuation of the inflammatory processes (27) . Therefore, the aim of the present study is to assess celecoxib, ketoprofen, and other NSAIDs effects in experimental colitis, verify which NSAIDs exacerbate the disease and contribute to the understanding of the mechanisms responsible for colitis reactivation.…”
Section: Introductionmentioning
confidence: 99%